Person-centred care for dementia patients (backend and frontend system) - Yap, Joon Shen (Nanyang Technological University, 2022)
Dementia is a syndrome that causes the loss of cognitive functioning at rates beyond normal aging. Some examples of the cognitive functioning that are affected include memory, attention, communication. Unfortunately, there is no known cure for dementia at the moment, but researchers have found that there exist other possibilities to delay the declination of cognitive functions through providing person-centered care to dementia patients. Person-centered care is a method where the healthcare providers and the patient interact with each other, with healthcare providers providing the patient with compassionate attention to improve the health condition of the patient. To assist the caregivers in providing effective care to the patients, the PEAR system is developed. PEAR is system developed to help the caretakers in the process of providing care to dementia patients by simplifying the tasks and procedures needed to be done during the process of treatment. PEAR provides a platform for coordination to all the stakeholders involved in the dementia treatment process which includes the caregiver, supervisor, game therapist, administrator, and guardian. The objective of the project is to inherit the PEAR system and improve its backend system that includes a web API (Application Programming Interface) and a web client. The main task of the project includes integration of DevOps operations into the backend system, design and implement test structure, create unit tests project, create UI test project, design and implement CI/CD workflow, Furthermore, create a set of guidelines on the DevOps operations to enable the team to have sufficient knowledge on DevOps operations to include it in their development process. Lastly, create a test guide to guide the team to create tests for their own features. The final product of the project is to create a full DevOps CI/CD workflow with unit testing and UI testing, complimented with a set of guides to allow future developers to follow.